Correlation of occlusal characteristics with mentolabial sulcus in patients at a tertiary care hospital: A cross-sectional study - Ashraf Khan, Ayesha; Sarah Irfan; Tabassum Ahsan Qadeer (Journal of the Pakistan Medical Association, 2025)
Objective: To find correlation of mentolabial sulcus depth and mentolabial sulcus angle with skeletal and dental characteristics. Method: The observational, cross-sectional study was conducted at the Department of Orthodontics, Bahria University Health Sciences, Karachi, from October 7, 2023, July 31, 2024, and comprised patients of either gender aged 18-25 years with having complete permanent dentition except third molars. Different skeletal, dental and soft tissue variables were measured from cephalometric radiograph. including mentolabial sulcus depth and mentolabial sulcus angle. Overjet, overbite, curve of Spee, incisor, canine and molar relationship were measured from the dental cast. The patients were divided into three groups on basis of mentolabial sulcus depth and mentolabial sulcus angle. Mentolabial sulcus depth was divided into Shallow, Average and Deep depth subgroups, while mentolabial sulcus angle was divided into Shallow, Average and Deep angle subgroups. Data was analysed using SPSS 23. Result: Of the 148 patients, 104(70.3%) were females and 44(29.7%) were males. The overall mean age was 20.75±2.47 years. The mean mentolabial sulcus depth was 5.86±2.10mm and mean mentolabial sulcus angle was 106.22±25.11°. The mean mentolabial sulcus depth was deeper in males than females (p<0.05). Overjet, class II canine and molar relationship, retruded mandible and bimax proclination were associated with deep mentolabial sulcus depth (p<0.05). When Shallow Angle was compared with Average and Deep angles, all vertical values were found increased in the Shallow Angle group (p<0.05). Conclusion: Male gender, class II malocclusion, increased overbite, bimax proclination and low facial height were associated with deep mentolabial sulcus, whereas increased facial height was associated with shallow mentolabial sulcus depth.